2006
DOI: 10.1002/ejoc.200600681
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Benzolactone Collection using Click Chemistry

Abstract: A collection of benzotriazoles consisting of seven compounds was prepared from the propynyl‐substituted benzolactone 1 and various azides using click chemistry. The lactone 1 was obtained through a short route by direct esterification of the allylbenzoic acid 9 with the alkynol 7 giving the benzoate 2. The homopropargyl alcohol 7 in turn was obtained by opening the epoxide 6 with triisopropylsilyl acetylide. Ring‐closing metathesis of the ester 2 using Grubbs catalyst II followed by removal of the silicon prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Based on the suspicion that the dienone moiety may be responsible for loss of in vivo activity (it has been shown that DTT rapidly inactivates radicicol by conjugate addition to the dienone) [59] a new analog was designed [64], which capitalizes on an extremely efficient copper catalyzed cycloaddition of an azide with an alkyne (Scheme 3) [65]. The efficiency and permissibility of this latter reaction had already inspired Maier and coworkers to use it for the generation of simpler resorcylide analogs [66]. Attesting to the efficiency of the click reaction and the synthetic design, the triazole-cycloproparadicicol could be obtained in only 11 steps (longest linear sequence) with 20% overall yield!…”
Section: Diverted Synthesis and Diversity-orien-ted Synthesis Of Natumentioning
confidence: 98%
“…Based on the suspicion that the dienone moiety may be responsible for loss of in vivo activity (it has been shown that DTT rapidly inactivates radicicol by conjugate addition to the dienone) [59] a new analog was designed [64], which capitalizes on an extremely efficient copper catalyzed cycloaddition of an azide with an alkyne (Scheme 3) [65]. The efficiency and permissibility of this latter reaction had already inspired Maier and coworkers to use it for the generation of simpler resorcylide analogs [66]. Attesting to the efficiency of the click reaction and the synthetic design, the triazole-cycloproparadicicol could be obtained in only 11 steps (longest linear sequence) with 20% overall yield!…”
Section: Diverted Synthesis and Diversity-orien-ted Synthesis Of Natumentioning
confidence: 98%
“…This way the triazoles 56 and 57 were obtained (Scheme 6). 40 These analogues showed cytotoxicity in the micromolar range, pointing to the crucial role of the enamide side chain in 31E.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…With the goal of developing an efficient DTS strategy toward salicylihalamide analogs, the Maier group has reported several routes to the macrocycle. Further, they produced a simplified macrocycle bearing an alkynyl side chain ( 83 ), leading to the production of several triazole analogs of type 84 using click chemistry (Scheme A) . In this example, the generation of the simplified macrocycle bearing a terminal alkyne ( 83 ) allowed for the coupling of a multitude of different azides.…”
Section: The Role Of Diverted Total Synthesis In Drug Discoverymentioning
confidence: 99%